Commercial advertising in Greek libraries - Koustas, Nikolaos; Koulouris, Alexandros; Kyprianos, Konstantinos; Vraimaki, Eftichia (Qualitative and Quantitative Methods in Libraries, 2019)
Libraries in Greece have lost much of their already limited funding due to the recent global economic crisis. It has therefore become necessary for them to seek alternative sources of income. One such strategy could be commercial advertising, which constitutes the renting of space within or outside the library or using the library’s website to place ads. However, an application of commercial advertising in libraries can trigger negative reactions from library patrons. In this context, the aim of this paper is to investigate stakeholders' views regarding the use of commercial advertising by Greek libraries, using a quantitative methodology. The results reveal that commercial advertising is considered as a profitable strategy for Greek libraries by both respondent groups, information professionals and users, alike.